Land Question And The Tribals Of Kerala - Nithya N.R (INTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH, 2013)
The paper seeks to examine the land question of tribals in Kerala, India. In the context of developing countries such as India, the state of Kerala has often been cited as a model. Notable among its achievements is the good health indicator in terms of mortality and fertility rates and high levels of utilization of formal health services and cent percent literacy. Later, it was observed that this model has several outlier communities in which tribal communities were the most victimized ones. The tribals are children of nature and their lifestyle is conditioned by the Ecosystem. After the sixty years of formation of the state tribals continues as one of the most marginalized community within the state, the post globalised developmental projects and developmental dreams of the state has again made the deprivation of the tribals of Kerala and the developmental divide has increased between the tribal and non-tribal in the state. The paper argues that deprivation of land and forests are the worst forms of oppression that these people experience.